Endotheliopathy syndromes, TA-TMA, and SOS, are risk factors for morbidity and mortality in critically ill pediatric hematopoietic cell transplant recipients - Goel, Shivani; Frost, Erin; Tarquinio, Keiko; Kamat, Pradip; Fitch, Taylor; Stenger, Elizabeth; Liu, Katie; Qayed, Muna; He, Zhulin; Westbrook, Adrianna; Williams, Kirsten M.; Schoettler, Michelle L. (Frontiers in Oncology, 2025)
BackgroundPediatric hematopoietic cell transplant (HCT) recipients who require intensive care unit (PICU) admission historically have high mortality rates. The HCT landscape is rapidly changing with the incorporation of novel graft versus host disease (GVHD), infection prevention strategies, and diagnosis and treatment of endothelial disorders—all potentially impacting the risk factors for morbidity and outcomes of critically ill pediatric HCT recipients.MethodsThis IRB-approved single-center, retrospective cohort included all allogeneic recipients from 2019 to 2023 who required ICU admission in the first year post-HCT.ResultsA total of 91 unique PICU admissions in 56 HCT patients were identified. The median age at HCT was 8.4 years; 30 (54%) were female. Moreover, 34 (61%) developed early endotheliopathy syndrome: 27 (48.2%) TA-TMA (all treated with eculizumab), 21 (37.5%) SOS (all treated with defibrotide), and 14 (25%) both TA-TMA and SOS. A total of 40 admissions (44%) required IMV. The risk factors (RF) for IMV included younger age, TA-TMA, SOS, RRT, and PICU length of stay ≥14 days. Of those requiring IMV, 15 patients (37.5%) failed extubation; no HCT or clinical features predicted extubation failure. Furthermore, 23 admissions (25.3%) required renal replacement therapy (RRT). The RF for RRT included TA-TMA, SOS, PICU LOS, and weight gain of ≥5% from dry weight at the time of PICU admission. The duration that weight exceeded 10% of the dry weight before RRT was associated with the inability to come off RRT. The 100-day PICU-related mortality was 25% (95% CI: 14–37), though the 1-year NRM from first ICU admission was 41% (95% CI: 31–51). RF for non-relapse-related mortality (NRM) included TA-TMA and required RRT. Grade 3–4 acute GVHD was not a risk factor for ICU morbidity nor mortality. Infection was also not a risk factor, but the very high proportion of infection in the cohort limits the analysis.DiscussionIn this contemporary cohort with a high prevalence of infection, the NRM of critically ill allogeneic HCT recipients was lower than the historic rates, and 62.5% of children requiring IMV were successfully extubated. SOS and TA-TMA were risk factors for highly morbid ICU complications and death despite early intervention. Alternative approaches to these diseases and their drivers and initiation of early RRT may avert death.